Knowledge, Attitude, and Perception about Autopsy among Community in Bandung - Aisyah Putri Pratiwi; Berlian Isnia Fitrasanti; Sani Tanzilah (Faculty of Medicine Universitas Padjadjaran, 2022)
Background: Autopsy is a comprehensive evaluation of the body and the circumstances surrounding an individual’s death. Currently, autopsy rates in various countries have been decreased in recent years. This decrease was due to the rejection by people who had inadequate knowledge, attitudes, and perceptions about autopsies. This study aimed to determine the knowledge, attitudes, and perceptions of Bandung residents about autopsies.Methods: This cross-sectional descriptive observational study involved people in the Bandung City who were over the age of 20 during the period August to September 2020. The sample was obtained using a snowball system. Research subjects filled out a questionnaire through a Google form containing questions about knowledge, attitudes, and perceptions. The results were categorized based on the median for each variable.Results: Subjects with questionnaire data obtained were 378 people with an average age of 30.30±13.48 years, and most (66.9%) were female. A total of 259 people had adequate knowledge (68.5%), 254 people (67.2%) had a positive attitude, and 249 people (65.9%) had a positive perception, with a median value of 7, 6, and 12, respectively. However, 95 people did not agree to do an autopsy on their relatives or family to determine the cause of death.Conclusion: The subject as a whole showed adequate knowledge, positive attitude, and perception. However, there are still some people who show inadequate knowledge and poor attitudes and perceptions about autopsies. It is recommended that the government and other institutions intervene in the community to increase knowledge and attitudes and improve public perception.